The effects of executive coaching on behaviors, attitudes, and personal characteristics: a meta-analysis of randomized control trial studies - Nicolau, Andreea; Candel, Octav Sorin; Constantin, Ticu; Kleingeld, Ad (Frontiers in Psychology, 2023)
Background A growing number of studies emphasize executive coaching as an effective developmental tool that managers can use to increase their performance in organizational settings. However, the coaching research suggests a large variety of processes and outcomes, lacking clarity on the primary psychological dimensions most impacted. Method Reviewing 20 studies with a rigorous methodological design that used control trials and pre-post tests, we evaluated and compared the relative effects of coaching on different types and sub-types of outcomes by means of a classification of coaching outcomes based on previously used taxonomies. Results The results indicate that the impact of coaching on behavioral outcomes was higher compared to attitudes and person characteristics outcomes, suggesting that behavioral coaching outcomes, especially cognitive behavioral activities, are the most impacted by executive coaching. Moreover, we found significant positive effects for some specific outcomes, such as self-efficacy, psychological capital, and resilience, indicating that executive coaching is effective in producing change even on dimensions considered relatively stable over time. The results show no moderation effects of the number of sessions. The length of the coaching program was a significant moderator only for the attitudes outcomes. Discussion These findings provide evidence that executive coaching is a powerful instrument for organizations to support positive change and personal development.